2020
DOI: 10.2196/21301
|View full text |Cite
|
Sign up to set email alerts
|

Association of Web-Based Physical Education With Mental Health of College Students in Wuhan During the COVID-19 Outbreak: Cross-Sectional Survey Study

Abstract: Background The COVID-19 outbreak has affected people’s health worldwide. For college students, web-based physical education is a challenge, as these course are normally offered outdoors. Objective The aim of this study was to use data from a web-based survey to evaluate the relationship between the mental health status of college students and their sports-related lifestyles. Problems related to web-based physical education were also examined. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
80
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(101 citation statements)
references
References 36 publications
7
80
1
5
Order By: Relevance
“…Of the identified studies, 21 studies meet the criteria [ 7 , 8 , 11 , 26 43 ]. Four studies had a prospective longitudinal design [ 29 , 32 , 39 , 42 ], 1 was a cross-sectional study with a retrospective measure of the exposure factor (henceforth treated as retrospective) [ 7 ], and 16 were cross-sectional studies [ 8 , 11 , 26 28 , 30 38 , 40 , 41 , 43 , 44 ]. A total of 7 studies were conducted in Asia [ 27 , 28 , 30 , 33 , 36 , 42 , 43 ], 6 in Europe [ 11 , 29 , 34 , 35 , 38 , 39 ], 3 in South America [ 8 , 31 , 32 ], 3 in North America [ 7 , 26 , 37 ], 1 in Oceania [ 41 ] and 1 study included a multinational sample [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the identified studies, 21 studies meet the criteria [ 7 , 8 , 11 , 26 43 ]. Four studies had a prospective longitudinal design [ 29 , 32 , 39 , 42 ], 1 was a cross-sectional study with a retrospective measure of the exposure factor (henceforth treated as retrospective) [ 7 ], and 16 were cross-sectional studies [ 8 , 11 , 26 28 , 30 38 , 40 , 41 , 43 , 44 ]. A total of 7 studies were conducted in Asia [ 27 , 28 , 30 , 33 , 36 , 42 , 43 ], 6 in Europe [ 11 , 29 , 34 , 35 , 38 , 39 ], 3 in South America [ 8 , 31 , 32 ], 3 in North America [ 7 , 26 , 37 ], 1 in Oceania [ 41 ] and 1 study included a multinational sample [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Out of ten studies reporting analyses on the association between the overall volume of PA and depression, seven studies showed that more PA is significantly associated with less depression symptoms [ 26 , 28 , 30 , 35 , 36 , 38 , 40 ], and three out of nine studies investigating the association between the overall volume of PA and anxiety symptoms showed that more PA is significantly associated with less anxiety symptoms [ 28 , 35 , 38 ]. Three out of six studies reported higher frequencies of PA to be significantly associated with less depression [ 30 , 32 , 39 ] and two out of five studies to be significantly associated with less anxiety [ 30 , 32 ]. One study showed that vigorous but not moderate PA is significantly associated with less depression and anxiety symptoms [ 8 ] and another study indicated that light and vigorous PA is significantly correlated with less depression, but moderate intensity was not [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, this meta-analysis included 84 studies with a total of 1 292 811 Chinese university students (Cao, 2020; Chang et al ., 2020; Chen et al ., 2020 a , 2020 b , 2020 c , 2020 d ; Chi et al ., 2020; Cong et al ., 2020; Deng et al ., 2020; Dong, 2020; Dong et al ., 2020; Feng, 2020; Feng et al ., 2020; Han et al ., 2020; Ji et al ., 2020; Jiang et al ., 2020; Lei et al ., 2020; Li and He, 2020; Li et al ., 2020 b ; Lian et al ., 2020; Liang et al ., 2020 a , 2020 b ; Lin and Xu, 2020; Lin et al ., 2020 a , 2020 b ; Liu, 2020 a , 2020 b ; Liu et al ., 2020 a , 2020 b , 2020 c ; Ma et al ., 2020 a , 2020 b ; Mao et al ., 2020; Qian, 2020; Ren et al ., 2020 a , 2020 b ; 2020 c ; Si et al ., 2020; Sun et al ., 2020, 2021; Tang et al ., 2020; Wan and Shao, 2020; Wang and He, 2020; Wang and Li, 2020; Wang et al ., 2020 b ; 2020 c ; 2020 d ; 2020 e ; 2020 f ; 2021; Wei, 2020; Wu et al ., 2020, 2021; Xiang et al ., 2020; Xiao et al ., 2020 a , 2020 b ; Xie et al ., 2020; Xin et al ., 2020; Xing et al ., 2020; Xiong et al ., 2020; Xu and Li, 2020; Yan et al ., 2020; Yang et al ., 2020 b ; Yao et al ., 2020; Yi et al ., 2020 a , 2020 b ; Yu et al ., 2020, 2021; Zhan et al ., 2020; Zhang et al ., 2020 b , 2020 c , 2020 d , 2020 ...…”
Section: Resultsmentioning
confidence: 99%
“…This is of particular concern given the experience of loneliness tends to be most common in young adults (Beam and Kim, 2020 ). However, professional physical guidance, especially in the context of online PA sessions, is needed for university students (Deng et al, 2020 ). Hence, the work of exercise professionals would be essential to ensure that PA programs are properly designed, monitored and implemented, which is of most importance to guarantee safety and efficacy of exercise training and long-term PA adherence (Natalucci et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%